Comparing the effectiveness of liquid based cytology with conventional PAP smear and colposcopy in screening for cervical cancer and it’s correlation with histopathological examination: a prospective study - Shanmugapriya, N.; Devika, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer remains worldwide the second most common cancer among women and is unique among human cancers, entirely attributable to infection. Although routine cytological screening has resulted in large reduction in the cervical cancer burden in our country, still the incidence rates continue to be unabated for want of effective screening programs. Methods: This is a prospective study which was conducted in the Department of Obstetrics and Gynecology. The study included 200 women who were randomly selected attending gynecology OPD and who fulfilled the inclusion criteria. All the selected patients were subjected to pap smear, LBC and colposcopy and histopathology done for suspected cases. Results: The differences of sensitivity and specificity between LBC, PAP smear and colposcopy in detection of premalignant lesions were analyzed using the chi square test. The sensitivity of LBC (89.5%) was significantly higher than sensitivity of PAP smear (47.37%). P <0.001. The specificity of PAP smear (95.06%) was higher than LBC (77.16%). The statistical analysis between LBC and PAP smear; LBC and colposcopy were significant (P=0.000<0.05). Conclusions: Liquid based cytology increases the sensitivity of cervical cancer detection and its ability to do molecular testing using the same sample. LBC also improves sample quality by reducing the number of unsatisfactory smears, reduces the number of false negative smears, causes reduction in interobserver bias and less time consuming.